Hubungan Komunikasi Interpersonal Tutor dengan Motivasi Belajar Peserta Didik Program Kesetaraan Paket C di PKBM Budi Utama Surabaya - Evania, Alma; Susilo, Heryanto (J+PLUS UNESA, 2024)
Students' learning motivation to encourage enthusiasm in achieving learning goals can be influenced by various factors, one of which is the tutor's interpersonal communication with students. The aim of this research is to determine the relationship between tutor interpersonal communication and students' learning motivation in the Package C at the Budi Utama Teaching and Learning Activity Center, Surabaya. This research uses quantitative correlational methods with analytical techniques Product Moment. The sample for this research was 32 students from the Package C at the Budi Utama Teaching and Learning Activity Center, Surabaya. Through the correlation test carried out, we obtained a correlation coefficient of 0.789 and a significance value of 0.000, which means that tutor interpersonal communication and student learning motivation have a positive relationship and are classified in the strong category, meaning that the learning motivation of students in the package C at the Budi Utama Teaching and Learning Activity Center in Surabaya on Indonesian language subjects can be determined by the tutor's communication with students. If the tutor's interpersonal communication is high, the student's learning motivation will also be high.